2014
DOI: 10.1016/j.jrp.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Random intercept EFA of personality scales

Abstract: HighlightsRandom Intercept EFA (RI-EFA) adjusts for acquiescence bias in self-reports.RI-EFA was examined with regard to the NEO-FFI and BFI personality scales.RI-EFA provides better model-to-data fit than standard CFA or EFA.The clarity of Big Five factor structures improves when applying RI-EFA.RI-EFA can be extended to further analytical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 15 publications
4
60
0
8
Order By: Relevance
“…To evaluate the relevance of acquiescence in personality questionnaires we analyzed data of a short instrument assessing the Big Five in two large scale studies representative of the adult population of the two countries. The results suggest that acquiescence accounts for about 4% of the variance of personality items, which is similar to what previous research has found (e.g., Aichholzer, 2014;Billiet & McClendon, 2000;Rorer & Goldberg, 1965). At first glance, this number suggests only a minor influence of acquiescence on personality items.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…To evaluate the relevance of acquiescence in personality questionnaires we analyzed data of a short instrument assessing the Big Five in two large scale studies representative of the adult population of the two countries. The results suggest that acquiescence accounts for about 4% of the variance of personality items, which is similar to what previous research has found (e.g., Aichholzer, 2014;Billiet & McClendon, 2000;Rorer & Goldberg, 1965). At first glance, this number suggests only a minor influence of acquiescence on personality items.…”
Section: Discussionsupporting
confidence: 90%
“…This can substantially bias correlations between items (Bentler et al, 1971), factor structures of personality inventories (Aichholzer, 2014;Rammstedt & Farmer, 2013), comparability of personality assessments across countries (Rammstedt, Kemper, & Borg, 2013) and (as shown in the present research) the suitability of underlying measurement models, and bias the correlation between personality items and criterion variables. Therefore, acquiescence should not be ignored (cf.…”
Section: Controlling Acquiescencementioning
confidence: 67%
See 3 more Smart Citations